67.0k views
4 votes
PLEASE HELP ~ 15 POINTS

Which expression is equivalent to (n^3/2 ÷ n^-1/6)
A. n^27
B. n^-27
C. n^-4
D. n^-5

1 Answer

6 votes

For this case we must simplify the following expression:


(\frac {n ^ {\frac {3} {2}}} {n ^ {- \frac {1} {6}}}) ^ {- 3}

By definition of power properties we have:


a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}

Then, rewriting the expression:


(n ^ {\frac {3} {2}} * n ^ {\frac {1} {6}}) ^ {- 3} =

To multiply powers of the same base, we put the same base and add the exponents:


(n ^ {\frac {3} {2} + \frac {1} {6}}) ^ {- 3} =\\(n ^ {\frac {18 + 2} {12}}) ^ {- 3} =\\(n ^ {\frac {20} {12}}) ^ {- 3} =\\(n ^ {\frac {5} {3}}) ^ {- 3} =

We multiply the exponents:


n ^ {\frac {-15} {3}} =\\n^(-5)

ANswer:

Option D

User AZhu
by
5.9k points